Primary ventriculo-peritoneal shunts in treatment of hydrocephalus associated with myelomeningocele - Stark, G. D. (1974)
In 50 children suffering from open myelomeningocele, a ventriculo-peritoneal shunt was employed as the primary procedure for control of hydrocephalus. In 11 cases the system was ultimately replaced by a ventriculo-atrial shunt, though this may not always have been necessary. In the remaining 39 patients satisfactory control of hydrocephalus was achieved. Obstruction, particularly of the peritoneal catheter, occurred frequently in the first 6 months but no revisions were required after 2 years. It is concluded that while ventriculo-peritoneal and ventriculo-atrial shunts achieve comparable success in controlling hydrocephalus, the former, due to the relatively innocuous complications, offers significant long-term advantages.